IMPLEMENTASI SISTEM PERADILAN BERBASIS ONLINE (E-COURT) DITENGAH PANDEMI COVID 19 DALAM PENYELESAIAN PERKARA PERDATA OLEH ADVOKAT DI PENGADILAN NEGERI SAMARINDA - Imron, Nathannael Stanlis (Universitas 17 Agustus 1945 Samarinda, 2022)
ABSTRACTSupreme Court Regulation Number 1 of 2019 or hereinafter abbreviated as PERMA Number 1 of 2019 is a revision of the previous Supreme Court Regulation, namely: Supreme Court Regulation Number 3 of 2018 concerning the Administration of Cases in Electronic Courts. service needs that are easier, cheaper, and more efficient. This service requirement is difficult to achieve without the support of information technology. Especially during a pandemic like now, the presence of PERMA is expected to be one of the answers to several problems faced by the community.The formulation of the problem in this study is what is the legal basis for the application of e-court by advocates in the settlement of civil cases in the general court in the city of Samarinda and how is the application of e-court by advocates in the settlement of civil cases at the Samarinda District Court. The type of research conducted by researchers is research that uses empirical juridical research methods where researchers can collect data through interviews.From the results of this study, it can be concluded that the e-court that occurred at the Samarinda District Court has met the effectiveness and is based on the law in a case that is more effective and efficient. Indicators of the effectiveness of e-court in this case can be seen from the fulfillment of a judicial institution that is simpler, faster, and cheaper when compared to the ordinary legal process. In litigation cases through e-court, both parties seeking justice and the court concerned get better benefits than litigation in the usual way, which can be seen from a simpler process, faster time so that from both cases the costs incurred are also more. spent. easier for justice seekers and also easier for advocates in the judicial process.Keyword : Justice System, E-Court, Samarinda District Court